'Small talk is not cheap': phatic computer-mediated communication in intercultural classes. Issue 5 (4th July 2017) - Maíz-Arévalo, Carmen
ABSTRACT: The present study aims to analyse the phatic exchanges performed by a class of nine intercultural Master's students during a collaborative assignment which demanded online discussion using English as a lingua franca (ELF). Prior studies on the use of phatic communication in computer-mediated communication have concentrated on social networking sites or micro-blogging (mostly Facebook or Twitter). Educational online tools, like the present e-forum, have received much less attention. Initially, I intended to answer three research questions: (i) Is phatic talk used in a transactional task? If so, what function(s) does it perform?, (ii) Is phatic talk affected by being computer-mediated rather than face-to-face? If so, in what ways? and (iii) How may an intercultural setting affect computer-mediated phatic talk? Results are preliminary but show that, despite the transactional character of the task, the students paid close attention to phatic communication as an essential way to build rapport and foster their collaboration as a group.